2020
DOI: 10.1101/2020.10.13.20211953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of drugs associated with reduced severity of COVID-19: A case-control study in a large population

Abstract: Background SARS-Cov-2 is a new virus causing a pandemic of primarily respiratory illness designated as Coronavirus Disease 2019 (COVID-19). This disease is associated with excess mortality, particularly among the elderly, raising concerns for public health. It is crucial to identify whether existing medications could protect against adverse outcomes of COVID-19 infection. Methods We performed a population-based study among members of Clalit Health Services (CHS), the largest healthcare provider in Israel. CHS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
2
20
0
2
Order By: Relevance
“…We further examined 26 full-text articles and searched the references of relevant articles, retrieving 2 additional publications. Finally, 22 studies met all inclusion criteria [ 1 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The flow diagram of the systematic articles search is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We further examined 26 full-text articles and searched the references of relevant articles, retrieving 2 additional publications. Finally, 22 studies met all inclusion criteria [ 1 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The flow diagram of the systematic articles search is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the Clalit Health Care System data warehouse records identified 8,681 adults with SARS-CoV-2 infection and hospitalization in Israel. Simultaneous analysis of linked outpatient pharmacy records identified a reduced likelihood for hospitalization in individuals taking medications known to interact with the cholesterol synthesis pathway, specifically ubiquinone (OR 0.25), ezetimibe (OR 0.51), and rosuvastatin (OR 0.75) in the 30 days prior to diagnosis ( Israel et al., 2020 ).…”
Section: Intracellular and Extracellular Cholesterol Lipids And Stamentioning
confidence: 99%
“…All studies were observational in design, with either a retrospective cohort study design or a case-control study design. Israel et al 16 split their database into two cohorts and reported two relative risk ratios for the outcome of mortality. Two studies, Grasselli et al 14 and Rodriguez-Nava et al 20 , reported on ICU patients; the other 11 7-10,13,15-19,21,22 reported on non-ICU patients.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, Grasselli et al 14 and Rodriguez-Nava et al 20 , reported on ICU patients; the other 11 7-10,13,15-19,21,22 reported on non-ICU patients. Six studies 7,10,17,18,20,21 defined a statin user as one who used statins after a COVID-19 hospitalization; seven studies 8,9,13-16,19,22 defined a statin user as one who used statins before a COVID-19 hospitalization.…”
Section: Resultsmentioning
confidence: 99%